2018
DOI: 10.1080/02656736.2018.1497209
|View full text |Cite
|
Sign up to set email alerts
|

Systematic quality assurance of the BSD2000-3D MR-compatible hyperthermia applicator performance using MR temperature imaging

Abstract: The Pyrexar BSD2000-3D MR-compatible applicator provides robust and reproducible heating. The upper boundary of the 95% confidence interval of the spatial steering accuracy is 0.9 cm, i.e. sufficient to fulfil the criterion of ≤0.2 °C temperature variation due to positioning errors as defined by Canters et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…The possibility to adapt/optimize SAR pattern in a phantom by employing MR thermometry in an iterative procedure were also shown for this applicator [47]. A recent more systematic quality assurance analysis of this system in a 1.5 T MRI scanner showed a mean maximum temperature increase (T increase, max ) in a Perfax homogeneous phantom of 5.9 ± 0.4 C, using 1000 W input power for 12.4 min, and a mean steering error of 0.4 ± 0.2 cm [44]. Clinical experiments in 15 patients [46] with pre-irradiated rectal recurrences showed significant correlation between the MRT-derived mean temperatures in the tumor with invasive measurements, tumor features (volume and location) and clinical response (p ¼ 0.04) [46].…”
Section: Decoupled Devices (Ht-only Inserts)mentioning
confidence: 73%
See 2 more Smart Citations
“…The possibility to adapt/optimize SAR pattern in a phantom by employing MR thermometry in an iterative procedure were also shown for this applicator [47]. A recent more systematic quality assurance analysis of this system in a 1.5 T MRI scanner showed a mean maximum temperature increase (T increase, max ) in a Perfax homogeneous phantom of 5.9 ± 0.4 C, using 1000 W input power for 12.4 min, and a mean steering error of 0.4 ± 0.2 cm [44]. Clinical experiments in 15 patients [46] with pre-irradiated rectal recurrences showed significant correlation between the MRT-derived mean temperatures in the tumor with invasive measurements, tumor features (volume and location) and clinical response (p ¼ 0.04) [46].…”
Section: Decoupled Devices (Ht-only Inserts)mentioning
confidence: 73%
“…After the early feasibility studies of diffusion-based MR thermometry methods, PRFS-based MRT methods were used in all studies. Spoiled gradient echo sequence with echo times close to the T2 Ã of muscle tissue is commonly used for PRFS-based MRT scans [44,49,60,62,64,68]. In addition to treatment monitoring, MRT also provides unique opportunities to validate EM models with 3D measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a thermal dose-effect relationship [12][13][14][15] strongly supports identical QA measurements among institutions to determine whether clinical results using these different systems can be meaningfully combined in multi-institution clinical studies [16]. We recently demonstrated that magnetic resonance thermometry (MRT) measurements, as facilitated by MR-radiofrequency (RF) hyperthermia systems, provide unprecedented 3D QA capabilities [17]. However, an anthropomorphic and human-shape representative phantom has not yet been utilized to compare results of multiple clinically active MR-compatible systems.…”
Section: Introductionmentioning
confidence: 91%
“…Second, temperature monitoring is currently performed using thermocouples inside or near the heated tissue [19], which only provides sparse spatial sampling of the temperature. Radiofrequency-based hyperthermia devices integrated into a magnetic resonance imaging (MRI) scanner could address some of above shortcomings and are currently evaluated for use in clinical settings [20,21].…”
Section: Introductionmentioning
confidence: 99%